Introduction to Migration and Refugee Flows: New Insights - Inmaculada Martínez-Zarzoso (Politics and Governance, 2021)
Population movements between countries and continents are not recent phenomena. What is new today is that migration flows are increasingly linked to the globalization process and to environmental degradation. Most of the migrants leave their homes for economic reasons, but also due to the higher frequency of natural disasters. Of the total migrant population, those who escape from conflicts or persecution still represent a smaller fraction and are entitled to obtain refugee status. This thematic issue includes eight articles that analyse migration flows and migration governance from different analytical perspectives. Five of the eight contributions examine the role that several factors play in explaining international migration flows and its effects, namely cultural diversity, information technology tools, governance, terrorism, and attitudes towards immigration. The remaining three articles are country studies that analyse the socio-economic causes/effects of migration flows to Portugal, Spain, and Germany, devoting special attention to forced migration and refugees.